Influence of physical attributes and pedotransfer function for predicting water retention in management systems - André C. Auler; Luiz F. Pires; Maria C. Pineda (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The aims of this study were to evaluate the effects of the soil structural physical attributes on the water retention and to develop pedotransfer functions (PTFs) for the estimation of the soil water content (θ) at different matric potentials of a Dystrophic Red Latosol (Hapludox) under conventional tillage (CT) and no-tillage (NT) soil management systems. The effects of long-term CT and NT (over 25 years) management on the soil bulk density (BD), total porosity (TP), macroporosity (Ma), microporosity (Mi) and water retention were investigated. The PTFs were developed to predict θ and used to evaluate the soil water retention curve only for the NT system. The NT system was characterized by smaller values of the soil BD and higher values of the soil TP and Mi than the CT system. The NT system exhibited a higher θ retained than the CT system for the pore-size interval of 0.2–30 μm. However, the CT system exhibited a large amount of water retention for pores smaller than 0.2 μm. The PTFs were utilized to estimate θ at matric potentials of -1, -3, -6, -10, -33, -100, -400, -800, and -1,500 kPa with adequate accuracy. The soil BD, Ma, Mi and sand content were the main variables considered to estimate θ for the different matric potentials evaluated.